The forgotten link: how the oral microbiome shapes childhood growth and development - Tjandrawinata, Raymond Rubianto; Amalia, Nurlinah; Tandi, Yosi Yohanes Putra; Athallah, Ariq Fadhil; Afif Wibowo, Caesaroy; Aditya, Muhammad Reva; Muhammad, Athaya Rahmanardi; Azizah, Maghfira Rahma; Humardani, Farizky Martriano; Nojaid, Ammar; Christabel, Jeremy Alvaro; Agnuristyaningrum, Alfi; et al. (Frontiers in Oral Health, 2025)
Childhood stunting, defined as impaired linear growth and development, remains a significant global health challenge with long-term consequences on cognitive and physical well-being. Emerging evidence highlights the pivotal role of the oral microbiome—a dynamic microbial ecosystem—in influencing nutritional status, immune response, and overall systemic health. This review explores the intricate interplay between the oral microbiome and stunting, emphasizing mechanisms such as microbial dysbiosis, its impact on nutrient absorption, and immune modulation. Disruptions in the oral microbiome can lead to nutrient malabsorption and systemic inflammation, further exacerbating growth impairments in children. Furthermore, the potential for microbiome-targeted diagnostics and interventions, including probiotics and prebiotics, offers novel strategies to address stunting. A deeper understanding of these interactions may inform innovative diagnostic tools and therapeutic interventions aimed at mitigating stunting through oral microbiome modulation. Integrating oral microbiome research into stunting prevention efforts could provide valuable insights for public health strategies to improve child growth and development, particularly in resource-limited settings. Future research should focus on elucidating the molecular pathways linking the oral microbiome to stunting and developing personalized interventions that optimize microbiome health in early life.